You are on page 1of 18

SERIES SOLUTIONS OF ODES WITH

VARIABLE COEFFICIENTS
Abstract. These notes describe the procedure for computing se-
ries solutions to ODEs with variable coecients.
Contents
1. Power series method 1
2. Frobenius method 7
1. Power series method
The power series method can be used to solve ODEs with variable
coecients. The resulting series can be used to study the solution to
problems for which direct calculation is dicult. The basic idea is to
approximate the solution with a power series of the form:
(1)

m=0
a
m
(x x
0
)
m
.
As an example consider the Taylor expansion of a function y about
a point x
0
, where the coecients a
m
are dened as
a
m
=
y
(m)
(x
0
)
m!
.
For y = e
x
the Taylor series about the point x
0
= 0 is given by
y(x) = e
x
=

m=0
y
(m)
(0)
m!
x
m
=

m=0
x
m
m!
.
To solve an ODE using the power series method we represent the
solution as a power series
y(x) =

m=0
a
m
(x x
0
)
m
,
and then plug the result into the given ODE to solve for the coecients
a
m
.
Date: Today is 10-31-12.
1
2 SERIES SOLUTIONS OF ODES
Example 1.1 (The basic idea). Consider the ODE y

y = 0, which
can be easily solved using separation of variables, giving the solution
y(x) = ce
x
= c
_

m=0
x
m
m!
_
.
To solve the ODE using the power series method we set
y(x) =

m=0
a
m
x
m
y

(x) =

m=1
ma
m
x
m1
.
Plugging y and y

into the ODE gives

m=1
ma
m
x
m1

m=0
a
m
x
m
= 0,
or

m=0
(m + 1)a
m+1
x
m

m=0
a
m
x
m
= 0,
such that if we collect powers of x, then

m=0
_
(m + 1)a
m+1
a
m
_
x
m
= 0.
Thus,
(a
1
a
0
) + (2a
2
a
1
)x + (3a
3
a
2
)x
2
+ ... = 0.
Note that 1, x, x
2
, ... are linearly independent and, thus,
(m + 1)a
m+1
a
m
= 0,
for all m. This, in turn, implies that
a
1
= a
0
, a
2
=
a
1
2
=
a
0
2!
, a
3
=
a
2
3
=
a
0
3!
, ... , a
m
=
a
m1
m
=
a
0
m!
.
Substituting these coecients into the original power series for y gives
y(x) =

m=0
a
m
x
m
=

m=0
a
0
m!
x
m
,
which for a
0
= c gives
y(x) = c

m=0
x
m
m!
= ce
x
.
Thus, we recovered the same solution that we found using separation
of variables. We note that the function y(x) = e
x
C

(R), that is,


this function is analytic and, so, it can be represented as a power series
obtained from Taylor expansion.
SERIES SOLUTIONS OF ODES 3
Convergence. An important question that arises now is: when does
the power series converge to the solution of the ODE?
Consider the series
s(x) =

m=0
a
m
(x x
0
)
m
,
and let the nth partial sum of the series be dened as
s
n
(x) =
n

m=0
a
m
(x x
0
)
m
.
Then, the remainder, R
n
(x), is dened as
R
n
(x) = s(x) s
n
(x) =

m=n+1
a
m
(x x
0
)
m
.
We dene convergence pointwise for xed values of x, say, x = x. The
series is convergent at x = x if
lim
n
s
n
( x) := s( x).
In terms of the remainder term, this gives for every n:
s( x) = s
n
( x) + R
n
( x).
If the sequence diverges, then the series is said to diverge.
Denition 1.2. The series s(x) =

m=0
a
m
(x x
0
)
m
is convergent
at x = x if for any positive > 0, there exists an N (depending on )
such that
[R
n
(x)[ = [s( x) s
n
( x)[ < for all n > N.
Thus, we require that
s( x) < s
n
( x) < s( x) +
for all n > N.
The convergence interval is the interval for which the series, s(x),
converges. Note that the series always converges for x = x
0
, since,
then all terms except for the rst one, a
0
, are equal to zero. The
convergence interval is thus dened as follows
[x x
0
[ < R,
where R denotes the radius of convergence such that s(x) converges
whenever x satises the above inequality. When [xx
0
[ > R, then the
series diverges.
4 SERIES SOLUTIONS OF ODES
Remark 1.3. The radius of convergence can be determined by evalu-
ating the limit
R =
1
lim
m

a
m+1
am

.
Example 1.4. For e
x
=

m=0
x
m
m!
, we have a
m
=
1
m!
. Thus,
a
m+1
a
m
=
1
m + 1
0 m ,
implying R = .
Theorem 1.5. If p, q, and r are analytic at x = x
0
, then every solution
of
y

+ p(x)y

+ q(x)y = r(x),
is analytic at x = x
0
and can be represented as a power series of xx
0
with a radius of convergence R > 0.
Legendres equation. We now consider another application of the
power series method for Legendres equation
(1 x
2
)y

2xy

+ n(n + 1)y = 0.
Note that if we divide the equation by 1 x
2
, then we obtain the
standard form as in Theorem 1.5, with
p(x) =
2x
1 x
2
, q(x) =
n(n + 1)
1 x
2
analytic at x = 0, so that a power series solution to the ODE exists in
the interval
[x[ < R,
for some R > 0.
As before, we substitute y(x) =

m=0
a
m
x
m
and its rst and second
derivatives into the ODE:
(1 x
2
)

m=2
m(m1)a
m
x
m2
2x

m=1
ma
m
x
m1
+ k

m=0
a
m
x
m
=

m=2
m(m1)a
m
x
m2

m=2
m(m1)a
m
x
m

m=1
2ma
m
x
m
+ k

m=0
a
m
x
m
=

m=0
(m + 2)(m + 1)a
m+2
x
m

m=2
m(m1)a
m
x
m

m=1
2ma
m
x
m
+

m=0
ka
m
x
m
= 0,
with k = n(n + 1). Thus,
2 1a
2
+ ka
0
= 0, 3 2 a
3
+
_
2 + k
_
a
1
= 0,
SERIES SOLUTIONS OF ODES 5
and
(m + 2)(m + 1)a
m+2
+
_
m(m1) 2m + k
_
a
m
= 0, m 2.
Thus,
a
2
=
k
2
a
0
, a
3
=
2 k
3!
a
1
and
a
m+2
=
m
2
+ mk
(m + 2)(m + 1)
a
m
=
(n m)(n + m + 1)
(m + 2)(m + 1)
a
m
, m 2. (2)
Plugging these coecients into the series for y gives
y(x) = a
0
y
1
(x) + a
1
y
2
(x),
where a
0
and a
1
are arbitrary constants and
y
1
(x) = a
1
0
(a
0
+a
2
x
2
+a
4
x
4
+...) and y
2
(x) = a
1
1
(a
1
+a
3
x
3
+a
5
x
5
+...).
Note that y
1
and y
2
are independent since one is a function of even
powers of x and another a function of odd powers of x.
Legendre polynomials. Note that if n is a positive integer, then for
m = n:
a
n+2
=
(n n)(n + n + 1)
(n + 2)(n + 1)
a
n
= 0,
and thus a
n+4
= 0, a
n+6
= 0, ... . Thus,
if n is an even and positive integer then y
1
(x) reduces to a
polynomial of degree n, and
if n is an odd and positive integer, then y
2
(x) reduces to a
polynomial of degree n.
The resulting polynomials for a certain choice of a
n
(such that p
n
(1) =
1) are the so called Legendre polynomials. To derive the coecients,
we set
a
n
=
(2n!)
2
n
(n!)
2
,
where n is a positive integer. (If n = 0, then we set a
0
= 1.) The
remaining nonzero coecients for m n 2 are then computed from
the recurrence relation (2):
a
m
=
(m + 2)(m + 1)
(n m)(n + m + 1)
a
m+2
.
The general closed form expression for the coecients when n2m 0
is
a
n2m
= (1)
m
(2n 2m)!
2
n
m!(n m)!(n 2m)!
.
6 SERIES SOLUTIONS OF ODES
See page 178 in the textbook for the derivation of the closed form
expression. The polynomial is then
p
n
(x) =
M

m=0
a
n2m
x
n2m
=
M

m=0
(1)
m
(2n 2m)!
2
n
m!(n m)!(n 2m)!
x
n2m
,
where M = n/2 or M = (n 1)/2. Later we will show that these
polynomials are orthogonal on the interval J = [1, 1].
The rst few Legendre polynomials are
p
0
(x) = 1.
p
1
(x) = x.
p
2
(x) =
1
2
(3x
2
1).
p
3
(x) =
1
2
(5x
3
3x).
...
The orthogonality of the polynomials is in the inner product dened as
f, g =
_
1
1
f gdx
Note that
p
0
, p
1
=
_
1
1
1 xdx = 0,
since x is an odd function. Note that a similar argument holds for p
1
and p
2
. If we consider for example p
0
and p
2
then we have
p
0
, p
2
=
1
2
_
1
1
1 (3x
2
1)dx =
1
2
_
x
3
x
_

1
1
= 0.
In similar way, one can show that
p
k
, p
l
= c
kl
,
where
kl
= 0 for k ,= l and
kl
= 1 for k = l. Such orthogonality
conditions are useful in constructing approximations to functions and
solving PDEs.
Note that the inner product f, g can be viewed as a mapping
, : 1 1 R,
where 1 is a vector space. Thus, the inner product gives extra structure
to a vector space, resulting in an inner product space. The inner prod-
uct satises certain axioms, which follow from its denition in terms of
integration: Given u, v, w 1 and R,
(1) u + v, w = u, w +v, w.
(2) v, w = v, w.
(3) v, w = w, v.
(4) v, v 0 and equality holds only for v = 0.
SERIES SOLUTIONS OF ODES 7
Later we will dene a vector norm induced by the inner product.
2. Frobenius method
The Frobenius method is an extension of the power series method
that can be applied when the coecients of the ODE are not analytic.
Given the ODE
y

+ p(x)y

+ q(x)y = 0,
the points x
0
for which p and q are analytic are regular points. All
other points are referred to as singular points.
The general form of the equation we consider is
y

+
v(x)
x
y

+
u(x)
x
2
y = 0,
where p(x) =
v(x)
x
and q(x)
u(x)
x
2
with u, v analytic. To solve this equa-
tion, we consider the equivalent form:
x
2
y

+ xv(x)y

+ u(x)y = 0,
and expand v and u such that:
v(x) = v
0
+ v
1
x + v
2
x
2
+ ... and u(x) = u
0
+ u
1
x + u
2
x
2
+ ... .
Then, we take
y(x) = x
r
_

m=0
a
m
x
m
_
,
and so
y

=
_

m=0
(m + r)a
m
x
m+r1
_
= x
r1

m=0
(m + r)a
m
x
m
,
and
y

=
_

m=0
(m+r)(m+r1)a
m
x
m+r2
_
= x
r2

m=0
(m+r)(m+r1)a
m
x
m
.
Plugging into the ODE gives (canceling the common x
r
term)
_

m=0
(m + r)(m + r 1)a
m
x
m
_
+
_

m=0
v
m
x
m
__

m=0
(m + r)a
m
x
m
_
+
_

m=0
u
m
x
m
__

m=0
a
m
x
m
_
= 0. (3)
When m = 0 this reduces to
r(r 1) + v
0
r + u
0
= 0,
8 SERIES SOLUTIONS OF ODES
which is referred to as the indicial equation. Note that v
0
= v(0)
and u
0
= u(0) are given and thus we can solve for the roots of this
quadratic equation. Three cases arise depending on the roots, r
1
, r
2
, of
this equation:
(1) Distinct roots not diering by an integer.
(2) Double root.
(3) Roots diering by an integer.
Remark 2.1. A technique that is typically applied together with the
Frobenius method is reduction of order. Specically, in certain cases
one computes the rst component of the general solution, y
1
, using
the indicial equation and then applies reduction of order to compute a
second independent solution as needed.
The basic approach is as follows. Given a linear dierential equation
y

+ p(t)y

+ q(t)y = 0
and a single solution y
1
(t), let the second solution be dened as
y
2
= v(t)y
1
(t)
where v(t) is an arbitrary function. Thus
y

2
= v

(t)y
1
(t) + v(t)y

1
(t)
and
y

2
= v

(t)y
1
(t) + 2v

(t)y

1
(t) + v(t)y

1
(t).
If these are substituted for y, y

, and y

in the dierential equation,


then
y
1
(t) v

+ (2y

1
(t) + p(t)y
1
(t)) v

+ (y

1
(t) + p(t)y

1
(t) + q(t)y
1
(t)) v = 0.
Now, since y
1
(t) is a solution of the original dierential equation,
y

1
(t) + p(t)y

1
(t) + q(t)y
1
(t) = 0, so we can reduce the equation to
y
1
(t) v

+ (2y

1
(t) + p(t)y
1
(t)) v

= 0
which is a rst-order dierential equation for v

(t) (reduction of order).


Dividing by y
1
(t) we obtain
v

+
_
2y

1
(t)
y
1
(t)
+ p(t)
_
v

= 0.
Hence we use the integrating factor
(t) = e

(
2y

1
(t)
y
1
(t)
+p(t))dt
= y
2
1
(t)e

p(t)dt
.
SERIES SOLUTIONS OF ODES 9
Multiplying the dierential equation with the integrating factor (t),
the equation in v(t) can be reduced to
d
dt
(v

(t)y
2
1
(t)e

p(t)dt
) = 0.
We integrate this equation and solve for v

(t) and then integrate the


result and plug this into the original equation for y
2
: y
2
= v(t)y
1
(t) ,
where v

(t) = y
2
1
e

p(t)dt
.
We now proceed to consider the rst two cases classied according
to the roots r
1
and r
2
of the incdicial equation. The third case is found
in the textbook.
Case 1: r
1
and r
2
are distinct roots not diering by an integer. A
basis for the solution to the ODE is
y
1
(x) = x
r
1
_
a
0
+a
1
x+a
2
x
2
+...

and y
2
(x) = x
r
2
_
A
0
+A
1
x+A
2
x
2
+...

,
with a
0
, a
1
, ... and A
0
, A
1
, ... are obtained by equating the coecients
of powers of x in (3):
_

m=0
(m + r)(m + r 1)a
m
x
m
_
+
_

m=0
v
m
x
m
__

m=0
(m + r)a
m
x
m
_
+
_

m=0
u
m
x
m
__

m=0
a
m
x
m
_
=
_
r(r 1)a
0
+ ...

+
_
v
0
+ v
1
x + ...
__
ra
0
+ ...
_
+
_
u
0
+ u
1
x + ...
__
a
0
+ a
1
x + ...
_
= 0.
Example 2.2. Consider the Euler-Cauchy equation:
x
2
y

+ v
0
xy

+ u
0
y = 0,
where u
0
and v
0
are constants. We set
y(x) = x
r
_

m=0
a
m
x
m
_
= x
r
,
i.e., we set a
0
= 1 and a
m
= 0, for m ,= 0, and set v(x) = v
0
and
u(x) = u
0
. Substituting into the ODE gives
r(r 1) + v
0
r + u
0
= 0.
For dierent roots, r
1
,= r
2
, we get y
1
= x
r1
and y
2
= x
r
2
.
Case 2: double root r
1
= r
2
. In this case,
r =
1
2
_
1 v
0
_
since r(r 1) + v
0
r + u
0
= r
2
+ (1 v
0
)r + u
0
.
A basis for the general solution is given by
y
1
(x) = x
r
1
_
a
0
+a
1
x+a
2
x
2
+...

and y
2
(x) = y
1
(x) ln x+x
r
2
_
A
0
+A
1
x+A
2
x
2
+...

,
10 SERIES SOLUTIONS OF ODES
where again the coecients are obtained by equating the coecients
of powers of x in (3), as needed.
Example 2.3. Consider the hypergeometric equation:
x
_
x 1
_
y

+ (3x 1)y

+ y = 0.
Substituting y(x) = x
r
_

m=0
a
m
x
m
_
and its derivatives into the equa-
tions gives
_

m=0
(m + r)(m + r 1)a
m
x
m+r
_

m=0
(m + r)(m + r 1)a
m
x
m+r1
_
+
3
_

m=0
(m + r)a
m
x
m+r
_

m=0
(m + r)a
m
x
m+r1
_
+
_

m=0
a
m
x
m+r
_
= 0.
The smallest power is x
r1
, giving
_
r(r 1) r

a
0
= 0 r
2
= 0.
Setting r = 0 gives
_

m=0
m(m1)a
m
x
m
_

m=1
m(m1)a
m
x
m1
_
+
3
_

m=0
ma
m
x
m
_

m=1
ma
m
x
m1
_
+
_

m=0
a
m
x
m
_
= 0,
implying
_

m=0
m(m1)a
m
x
m
_

m=0
(m + 1)ma
m+1
x
m
_
+
3
_

m=0
ma
m
x
m
_

m=0
(m + 1)a
m+1
x
m
_
+
_

m=0
a
m
x
m
_
= 0.
Thus,
_
m(m1) + 3m + 1

a
m

_
(m + 1)m + (m + 1)

a
m+1
= 0,
Now, since
m(m1) + 3m + 1 = m
2
+ 2m + 1 = (m + 1)m + (m + 1),
it follows that a
m+1
= a
m
. Thus, for a
0
= 1, we have
y
1
(x) =

m=0
x
m
=
1
1 x
.
SERIES SOLUTIONS OF ODES 11
The second independent solution is obtained by reduction of order,
which gives
y
2
(x) =
ln x
1 x
.
This follows since

_
pdx =
_
3x 1
x(x 1)
dx =
_ _
2
x 1
+
1
x
_
dx = 2 ln(x1)ln x.
Thus,
v

= y
2
1
e

pdx
=
(x 1)
2
(x 1)
2
x
=
1
x
v = ln x y
2
= vy
1
=
ln x
1 x
.
Bessels equation. Here we consider Bessels equation, given by the
following ODE
x
2
y

+ xy

+ (x
2
v
2
)y = 0,
where R. The equation often results from simplifying a cylindri-
cally symmetric PDE. Dividing the equation by x
2
gives
y

+
y

x
+
x
2

2
x
2
y = 0,
which is the standard form needed for the Frobenius method. To nd
the solution we substitute
y(x) = x
r
_

m=0
a
m
x
m
_
,
into the ODE, giving

m=0
(m + r)(m + r 1)a
m
x
m+r
+

m=0
(m + r)a
m
x
m+r
+

m=0
a
m
x
m+r+2

m=0
a
m
x
m
= 0.
We obtain the indicial equation when m = 0:
r(r 1)a
0
+ ra
0

2
a
0
= 0 (r )(r + ) = 0.
Thus, the roots are r
1
= and r
2
= . To compute the coecients
of the series representation of y, we equate the coecients of powers of
x, with r = . For m = 1 we have
( + 1)a
1
+ ( + 1)a
1

2
a
1
= 0 a
1
= 0,
since 0, implying that a
3
= 0, a
5
= 0,... Last, for m 2 we have
(m + 2)ma
m
+ a
m2
= 0,
12 SERIES SOLUTIONS OF ODES
since
(m + )(m + 1) + (m + )
2
= (m + )
2

2
= m
2
+ 2m.
Thus,
(2m + 2)2ma
2m
+ a
2m2
= 0,
or
a
2m
=
1
2
2
m( + m)
a
2m2
.
Thus,
a
2
=
a
0
2
2
( + 1)
, a
4
=
a
2
2
2
2( + 2)
=
a
0
2
4
2!( + 1)( + 2)
,
and in general
a
2m
=
(1)
m
a
0
2
2m
m!( + 1)( + 2) . . . ( + m)
.
The form of the Bessel functions depends on the value of .
Case 1: = n is an integer we have
a
2m
=
(1)
m
a
0
2
2m
m!(n + 1)(n + 2) . . . (n + m)
.
Letting
a
0
=
1
2
n
n!
,
we get
a
2m
=
(1)
m
2
2m+n
m!(n + m)!
,
and the solution to Bessels equation is given by
J
n
(x) = x
n

m=0
(1)
m
x
2m
2
2m+n
m!(n + m)!
,
referred to as the Bessel function of order n. Note that convergence is
rapid, since the coecients decay rapidly.
Example 2.4. For n = 0 we have
J
0
(x) =

m=0
(1)
m
x
2m
2
2m
(m!)
2
= 1
x
2
2
2
(1!)
2
+
x
4
2
4
(2!)
2

x
6
2
6
(3!)
2
. . .
For n = 1 we have
J
1
(x) =

m=0
(1)
m
x
2m+1
2
2m+1
m!(m + 1)!
=
x
2

x
3
2
3
1!2!
+
x
5
2
5
2!3!

x
7
2
7
3!4!
+ . . .
SERIES SOLUTIONS OF ODES 13
Note that these series resemble the Taylor series of the sine and
cosine functions:
sin x =

n=0
(1)
n
(2n + 1)!
x
2n+1
= x
x
3
3!
+
x
5
5!
for all x,
and
cos x =

n=0
(1)
n
(2n)!
x
2n
= 1
x
2
2!
+
x
4
4!
for all x.
Figure 1. Bessel functions of the rst kind for = n.
Case 2: R
+
. When is any positive real number the concept
of factorial notation needs to be generalized in order to dene the
coecients of the Bessel functions. In general, the denition uses the
function:
( + 1) =
_

0
e
t
t

dt.
Integration by parts gives
( + 1) = e
t
t

0
+
_

0
e
t
t
1
dt = 0 + ().
Note that
(1) =
_

0
e
t
= e
t

0
= 1, (2) = 1(1), (3) = 2(2) = 21(1),
14 SERIES SOLUTIONS OF ODES
and in general
(n + 1) = n (n) = n! (1) = n!,
so that this denition coincides in the case when = n is an integer.
With this denition of the function, we have
J

(x) = x

m=0
(1)
m
x
2m
2
2m+
m!( + m + 1)
,
which is the Bessel function of rst kind of order . The series converges
for all x since
R =
1
lim
m

a
m+1
am

=
1
lim
m

2
2
(m+1)

= .
Example 2.5. Bessel functions with =
n
2
. We consider the case
n =
1
2
. We rst show that (
1
2
) = . Substitution gives

_
1
2
_
=
_

0
e
t
t
1
2
dt = 2
_

0
e
u
2
du,
where t = u
2
and du = 2udt. Squaring both sides of the expression
gives:

_
1
2
_
2
= 4
_

0
e
u
2
du
_

0
e
v
2
dv = 4
_

0
_

0
e
(u
2
+v
2
)
du dv.
Using polar coordinates (r, ) and letting u = r cos and v = r sin ,
such that du dv = r dr d, gives

_
1
2
_
2
= 4
_
2
0
_

0
e
r
2
rdrd = 4

2
_

0
e
r
2
rdr = 2
_

2
_
e
r
2

0
= .
SERIES SOLUTIONS OF ODES 15
We now consider =
1
2
, such that
J1
2
(x) = x
1
2

m=0
(1)
m
x
2m
2
2m+
1
2
m!
_
m +
3
2
_
=
_
2
x

m=0
(1)
m
x
2m+1
2
2m+1
m!
_
m +
3
2
_
= =
_
2
x

m=0
(1)
m
x
2m+1
_
2
m
m!
__
2
m+1

_
m +
3
2
_
_
=
_
2
x

m=0
(1)
m
x
2m+1
_
2m + 1
_
!

=
_
2
x
sin x,
where we used that

_
m +
3
2
_
=
_
m +
1
2
__
m
1
2
_
. . .
3
2

1
2

_
1
2
_
,
_
1
2
_
=

.
Similarly,
J

1
2
(x) =
_
2
x
cos x.
The general solution. To construct a general solution we need to
independent solutions to the ODE. We note that if J

(x) is a solu-
tion to the ODE, then so is J

(x), since the coecient that appears


in Bessels equation is
2
. We thus need to determine if J

(x) and
J

(x) are linearly independent solutions. As we show below, they are


independent when ,= n and dependent when = n, where n is an
arbitrary positive integer.
The result follows by considering the function used in dening the
coecients of J

(x) and
J

(x) = x

m=0
(1)
m
x
2m
2
2m
m!( + m + 1)
.
We note that for < 0, we dene
() =
( + k + 1)
( + 1)( + 2)...( + k)
,
where k is the smallest positive integer such that +k +1 > 0. Thus,
for = n and m < n, n + m + 1 < 0 and the coecients a
m
= 0
16 SERIES SOLUTIONS OF ODES
and, for, m = n, (1) = 1 implying the coecient a
n
,= 0:
J
n
(x) =

m=n
(1)
m
x
2mn
2
2mn
m!(n + m + 1)
=

m=n
(1)
m
x
2mn
2
2mn
m!(n + m)!
=

m=0
(1)
m+n
x
2m
2
2m
(m + n)!m!
= (1)
n

m=0
(1)
m
x
2m
2
2m+n
(m + n)!m!
= (1)
n
J
n
(x).
Thus, when = n, J

(x) and J

(x) are linearly dependent. However,


when is not an integer, then they are linear independent and the
general solution is
y(x) = c
1
J

(x) + c
2
J

(x).
Bessel functions of the second kind. The general solution of Bessels
equation for any value of is given by taking as a basis the Bessel func-
tion of the rst kind, J

(x) and the Bessel function of the second kind,


Y

(x), dened as
Y

(x) =
1
sin
_
J

(x) cos J

(x)

(4)
Y
n
(x) = lim
n
Y

(x). (5)
The Bessel functions of the second kind are again computed using the
Frobenius method. Seee pages 196-199 of the text for a discussion.
Note that for ,= n, J

(x) and Y

(x) since Y

(x) contains J

(x). Foe
= n one inserts J

(x) and J

(x) into the denition of Y

(x) and
then takes the limit n, which gives a solution of the form
Y
n
(x) =
2

J
n
(x)
_
ln
x
2
+
_
+
x
n

m=0
(1)
m1
_
h
m
+ h
m+n
_
2
2m+n
m!(m + n)!
x
2m

x
n

n1

m=0
(n m1)!
2
2mn
m!
x
2m
,
where x > 0, h
0
= 0, h
1
= 1, h
m
= 1 +
1
2
+ ... +
1
m
, and h
m+n
=
1 +
1
2
+ ... +
1
m+n
.
Since, in this case, Y
n
contains a logarithmic term, this solution is
linearly independent from J

and thus we have the general solution for


SERIES SOLUTIONS OF ODES 17
any > 0:
y(x) = c
1
J

(x) + c
2
Y

(x).
Example 2.6. Consider the Bessel equation
x
2
y

+ xy

+ (x
2
16)y = 0.
Then, = 4 and
y(x) = c
1
J
4
(x) + c
2
Y
4
(x).
Consider the ODE
xy

+ 5y

+ xy = 0.
Using the substitution y =
u
x
2
we obtain a Bessel equation from the
ODE. Here, we substitute y, y

= u

x
2
2ux
3
, and y

= u

x
2

4u

x
3
+ 6ux
4
into the equation:
u

x
1
4u

x
2
+ 6ux
3
+ 5u

x
2
10ux
3
+ ux
1
= 0.
Multiplying by x
3
gives
u

x
2
+ u

x 4u + ux
2
0
or
x
2
u

+ xu

+ (x
2
4)u = 0.
Thus, = 2 and the solution is given by
y(x) = c
1
J
2
(x) + c
2
Y
2
(x).
Note we could not use J
2
(x), since this is not independent from J
2
(x).
We conclude with two theorems on the series solutions to Bessels
equation.
Theorem 2.7. Consider the ODE
y

+
v(x)
x
y

+
u(x)
x
2
y = 0,
where R. Assume that v(x) and u(x) are analytic at x = 0. Then
at least one solution of the form
y(x) = x
r

m=0
a
m
x
m
,
and another linearly independent solution of the same form (with dif-
ferent r and coecients a
m
) or may contain a logarithmic term.
18 SERIES SOLUTIONS OF ODES
Theorem 2.8. Let W(, ) denote the Wronskian determinant. Then,
for Bessel functions of the rst kind, J

(x) and J

(x) and of the second


kind Y

(x) we have
W(J

(x), J

(x)) =
sin
x
and W(J

(x), Y

(x)) =
2
x
.

You might also like